2001
DOI: 10.4049/jimmunol.167.11.6637
|View full text |Cite
|
Sign up to set email alerts
|

IFN-γ Affects Homing of Diabetogenic T Cells

Abstract: IFN-γ is a cytokine with pleiotropic functions that participates in immune and autoimmune responses. The lack of IFN-γ is known to delay the development of autoimmune diabetes in nonobese diabetic (NOD) mice. Splenocytes from diabetic NOD and IFN-γ knockout (KO) NOD mice transfer diabetes into NOD recipients equally well. However, adoptive transfer of diabetogenic T cells from NOD mice into NOD.IFN-γ-KO or NOD mice lacking β-chain of IFN-γ receptor (NOD.IFN-γRβ-KO) appeared to be much less efficient. We found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
84
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(95 citation statements)
references
References 61 publications
11
84
0
Order By: Relevance
“…Interferon-γ may be an important factor involved in the induction of MAdCAM-1 expression in islets of Langerhans [33]. Experimental diabetes models using different IFNγ-deficient mice have shown that this cytokine is crucial in controlling the homing of diabetogenic T cells into islets [34,35]. In the absence of IFNγ, diabetogenic T cells accumulate in the exocrine tissue or at the islet vascular isthmus, comparable to the histological results presented in this study.…”
Section: Discussionsupporting
confidence: 88%
“…Interferon-γ may be an important factor involved in the induction of MAdCAM-1 expression in islets of Langerhans [33]. Experimental diabetes models using different IFNγ-deficient mice have shown that this cytokine is crucial in controlling the homing of diabetogenic T cells into islets [34,35]. In the absence of IFNγ, diabetogenic T cells accumulate in the exocrine tissue or at the islet vascular isthmus, comparable to the histological results presented in this study.…”
Section: Discussionsupporting
confidence: 88%
“…IFN-γ plays an important role in establishing insulitis and maintaining diabetogenic activity of the islet infiltrate by in part regulating the production of recruitment/retention cues, such as adhesion molecules and chemokines by islet resident cells (50). Indeed, suppression of IFN-γ by YTS resulted in decreased expression of chemokines, including IFN-γ-regulated CXCL9 and 10 ( Figure 2F).…”
Section: Discussionmentioning
confidence: 99%
“…There are a number of ways in which IFN-g could be envisaged to contribute to the disease process including by up-regulating expression of major histocompatibility complex (MHC) classes I and II, facilitating macrophage activation, and increasing leucocyte extravasation by inducing adhesion molecules and chemokines (reviewed in [15]). Indeed IFN-g has been implicated in promoting the homing of diabetogenic T cells to the pancreatic islets in the NOD mouse [16]. There is also a substantial literature directly implicating the IFN-g signalling pathway in beta cell death, the critical destructive event at the heart of autoimmune diabetes.…”
Section: The Th1 Paradigm In T1dmentioning
confidence: 99%
“…IFN-g drives a persistent signal in pancreatic beta cells that can be inhibited by overexpression of suppressor of cytokine signalling-1 (SOCS1) [17], and islet expression of SOCS1 was found to be protective in the rat insulin promoter-lymphocytic choriomeningitis virus (RIP-LCMV) mouse model of diabetes [18]. Both IFN-g -/- [16] and IFN-gR -/- [19] islets are killed less effectively in vitro by CD8 T cells [16] and cytokines [19]. It is particularly striking that beta cells lacking IFN-gR show reduced sensitivity not just to IFN-g induced death, but also to TNF-a-and IL-1b-induced death [19], highlighting the capacity of IFN-g to sensitize beta cells to multiple potential death triggers.…”
Section: The Th1 Paradigm In T1dmentioning
confidence: 99%